1970
DOI: 10.1017/s0043174500079674
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity, Movement, and Persistence of Soil-Incorporated Herbicides in Carrot Plantings

Abstract: The comparative performances of several herbicides incorporated 2.5 cm deep and unincorporated in furrow-irrigated soil were studied in four field experiments. Among eight herbicides evaluated,a,a,a-trifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine (trifluralin) was the most effective herbicide and controlled redroot pigweed (Amaranthus retroflexusL.), Palmer amaranth (Amaranthus palmeriS. Wats.), common purslane (Portulaca oleraceaL.), and barnyardgrass (Echinochloa crusgalli(L.) Beauv.) when incorporated, witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 6 publications
3
19
0
Order By: Relevance
“…The results of this study conform with findings of some other workers as the time required for the disappearance of phytotoxic residues in most of our trials is comparable to those obtained by Allott (1970) and Gardiner et al (1967) for terbacil and by Menges & Hubbard (1970), Probst et ai. (1967 and Schweizer & Holstun (1966) for trifluralin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study conform with findings of some other workers as the time required for the disappearance of phytotoxic residues in most of our trials is comparable to those obtained by Allott (1970) and Gardiner et al (1967) for terbacil and by Menges & Hubbard (1970), Probst et ai. (1967 and Schweizer & Holstun (1966) for trifluralin.…”
Section: Discussionsupporting
confidence: 93%
“…Both trifluralin and terbacil are known to have a long persistence in the soil, but the published reports show marked variability in the time required for their disappearance below phytotoxic levels. The concentration of trifluralin decreased to 10-15% of that applied within a half to one year (Probst et al, 1967) and toxic residues from the recommended rates disappeared within 5-7 months (Schweizer & Holstun, 1966;Menges & Hubbard, 1970). However, some other workers found that trifluralin persisted for more than a year in their trials (Rahman & Ashford, 1973;Wiese et al, 1969).…”
Section: Introductionmentioning
confidence: 98%
“…Onion competes poorly with weeds and is susceptible to most herbicides (9,11). Many summer annual weeds in vegetables have been controlled selectively with bensulide [O,O-diisopropyl phosphorodithioate S -ester with N -(2 -mercaptoethyl) benzenesulfonamide] and DCPA (dimethyl tetrachloroterephthalate) (10,11), but winter annuals including London rocket, common sunflower, ragweed parthenium, and annual sowthistle are resistant to these soil-applied herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…There has been little direct research on the effect of soil types on the DCPA degradation. However, many reports on the minimal movement of DCPA in the soil profile suggest that there may be a high chance of DCPA adsorption to soil, particularly organic matter or clay (Hurto and Turgeon, 1979;Mazur et al, 1969;Menges and Hubbard, 1970;Miller et al, 1978). If we assume high adsorption of DCPA to clay, a slower degradation rate can be expected from a soil with a higher clay content, leaving DCPA less available for microorganism decomposition.…”
Section: Soil Texture Effectmentioning
confidence: 99%
“…DCPA, introduced in 1959, has been used in a wide range of crops including turf (Weed Science Society of America, 1983). Many studies have been conducted to examine the performance of DCPA under different cropping conditions, reporting effective suppression of annual weed germination by DCPA (Menges and Hubbard, 1970;Miller et al, 1978;. However, inconsistent control in comparison to other preemergence herbicides was repmted by Johnson (1976).…”
mentioning
confidence: 99%